Palliative first-line therapy with weekly high-dose 5-fluorouracil and sodium folinic acid as a 24-hour infusion (AIO regimen) combined with weekly irinotecan in patients with metastatic adenocarcinoma of the stomach or esophagogastric junction followed by secondary metastatic resection after downsizing - Koucky, Kathrin (International Scientific Literature, Inc., 2011)
BACKGROUND: The aim of this retrospective study was to evaluate the efficacy and safety of weekly high-dose 5-fluorouracil (5-FU)/folinic acid (FA) as 24-h infusion (AIO regimen) plus irinotecan in patients with histologically proven metastatic gastroesophageal adenocarcinoma (UICC stage IV). MATERIAL/METHODS: From 08/1999 to 12/2008, 76 registered, previously untreated patients were evaluable. Treatment regimen: irinotecan (80 mg/m(2)) as 1-h infusion followed by 5-FU (2000 mg/m(2)) combined with FA (500 mg/m(2)) as 24-h infusion (d1, 8, 15, 22, 29, 36, qd 57). RESULTS: Median age: 59 years; male/female: 74%/26%; ECOG ≤1: 83%; response: CR: 1%, PR: 16%, SD: 61%, PD: 17%, not evaluable in terms of response: 5%; tumor control: 78%; median OS: 11.2 months; median time-to-progression: 5.3 months; 1-year survival rate: 49%; 2-year survival rate: 17%; no evidence of disease: 6.6%; higher grade toxicities (grade 3/4): anemia: 7%, leucopenia: 1%, ascites: 3%, nausea: 3%, infections: 12%, vomiting: 9%, GI bleeding of the primary tumor: 4%, diarrhea: 17%, thromboembolic events: 4%; secondary metastatic resection after downsizing: 16 patients (21%), R-classification of secondary resections: R0/R1/R2: 81%/6%/13%, median survival of the 16 patients with secondary resection: 23.7 months. CONCLUSIONS: Combined 5-FU/FA as 24-h infusion plus irinotecan may be considered as an active palliative first-line treatment accompanied by tolerable toxicity; thus offering an alternative to cisplatin-based treatment regimens. Thanks to efficient interdisciplinary teamwork, secondary metastatic resections could be performed in 16 patients. In total, the patients who had undergone secondary resection had a median survival of 23.7 months, whereas the median survival of patients without secondary resection was 10.1 months (p≤0.001).